Exploration on factors influencing HLA-C molecular expression level by flow cytometry - LI Yunan; JIANG Renhui; CAI Siqi; LIU Jie; DENG Zhihui (Zhongguo shuxue zazhi)
[Objective] To investigate the factors influencing the detection of HLA-C expression by flow cytometry. [Methods] A total of 12 hematopoietic stem cell suspension samples from peripheral hematopoietic stem cell volunteer donors were randomly collected after CD34+ cell counting detection. The influence of detecting different number of nucleated cell (500 000, 50 000 and 5 000), sequential order of red blood cell lysis and antibody incubation, and the HLA-C antibody with varied remaining time from the expiration date on the detection results of HLA-C expression by flow cytometry were investigated, respectively. The significance of differences between different groups was analyzed through Student t test. [Results] There was no significant difference in the proportion of HLA-C positive cells and mean fluorescence intensity (MFI) among the three groups with different nucleated cell numbers detected (500 000, 50 000 and 5 000) (P>0.05). The sequential order of red blood cell lysis and antibody incubation had no influence on the proportion of HLA-C positive cells (P>0.05), but HLA-C MFI value was significantly lower when antibody incubation was performed after red blood cell lysis than that when antibody incubation was performed before red blood cell lysis (P<0.05). The proportion of HLA-C positive cells and MFI value detected by HLA-C antibody remaining 24 months from the expiration date were significantly higher than those detected by HLA-C antibody remaining only 5 months from the expiration date (P<0.05). [Conclusion] The present study has investigated the factors of influencing HLA-C expression level by flow cytometry, the results have important reference and application value for standardizing the experimental operation of HLA-C expression and improving the accuracy and comparability of detection results.